Virtual emotions and Criminal Law - González-Tapia, María Isabel (Frontiers in Psychology, 2023)
This article examines the role that Criminal Law should play in regulating the non-therapeutic use of immersive Virtual Reality (VR), specifically its massive use by consumers. The starting point has been to consider VR as an intermediate risk scenario, for the purposes of Criminal Law, between the criminality entirely generated in the physical world and that developed in the 2D digital environments (cybercrimes and criminality linked to social networks and persuasive Artificial Intelligence (AI).Firstly, specialize literature has been analyzed to establish the nature of virtual reality. From a technical standpoint, virtual reality is a neurotechnology infused with high-risk artificial intelligence; an inseparable synthesis of non-invasive neurotechnology and a set of AI systems, considered highrisk for the fundamental rights of citizens. From the perspective of its functioning, VR is a "transformative" neurotechnology capable of altering what people perceive as reality. This is possible, because its realism lies in the emotional immersion of the user in the virtual experience, similarly to how our brain functions. Therefore, the key idea in the immersive functioning of virtual reality is its capacity to evoke and modify human emotions, which results its greater harmful potential compared to the 2D environment. From there, three central and specific areas of (legally unaddressed) risk arise: (1) the special comprehensive nature of the data collected and stored during its use; (2) its ability to mentally reproduce the "physical" experience of the avatar in the user; and(3) its significant capacity to manipulate individuals.Secondly, the paper examines both the reported cases and the foreseeable criminality in virtual worlds or "proto-metaverse", focusing on the three risk areas, and exemplifying them with attacks on mental privacy, sexual freedom, and consumer manipulation. Finally, it is proposed that Criminal Law should also intervene (as soon as possible) to define the "red lines" of massive virtual reality use by citizens. With a democratic and human-centered approach, a basic legal framework is outlined for the criminalization of specific harms and risks associated with virtual reality, adapting the existing legal framework as necessary.